Molecular Docking of Potential Inhibitors of Broccoli Myrosinase - Castillo-Nara, A; Mahn-Osses, A; Roman-Aliste, J (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Glucosinolates are secondary metabolites occurring in Brassicaceae plants whose hydrolysis may yield isothiocyanates, widely recognized as health-promoting compounds. Myrosinase catalyzes this conversion. The chemical mechanism involves an unstable intermediary (thiohydroxamate-O-sulfonate) that spontaneously decomposes into isothiocyanates or other non-bioactive compounds depending on pH and cofactors. At acidic pH, non-bioactive compounds such as nitriles and thiocyanates are formed, while at neutral pH isothiocyanates are obtained. Broccoli myrosinase has been poorly studied so far. Recently, its amino acidic sequence was elucidated, and a structural model was built. The aim of this work was to study the molecular interaction of broccoli myrosinase with different ligands at acidic pH to propose possible inhibitors that prevent formation of undesirable compounds at acidic pH, and that at neutral pH dissociate from the enzyme, allowing formation of isothiocyanates. The interaction between broccoli myrosinase and 40 ligands was studied by molecular docking simulations. Both the enzyme and each inhibitor were set at pH 3.0. Amygdaline and arbutin showed the highest affinity to broccoli myrosinase in this condition. The residues that stabilize the complexes agree with those that stabilize the substrate (Gln207, Glu429, Tyr352, and Ser433). Accordingly, amygdaline and arbutin would perform as competitive inhibitors of myrosinase at pH 3.0. © 2018 by the authors.